2019
DOI: 10.1016/j.devcel.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Sirtuin 1 Alters the Secretome of Breast Cancer Cells by Impairing Lysosomal Integrity

Abstract: Highlights d SIRT1 expression is frequently decreased in aggressive breast cancers d Reducing SIRT1 levels in breast cancer cells impairs lysosomal acidification d Loss of SIRT1 gives rise to a secretome that promotes cell invasion and survival d SIRT1 mediates these effects by regulating V-ATPase expression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(122 citation statements)
references
References 62 publications
9
113
0
Order By: Relevance
“…3I). Thus, our data consistently demonstrated that SIRT1 loss causes lysosomal de-acidification and is responsible for sEV overproduction via ATP6V1A downregulation in SEN cells, a mechanism reported for certain cancer cell types 35 .…”
Section: Sirt1 Decline Supports Deficient Lysosomal Acidification Andsupporting
confidence: 81%
See 3 more Smart Citations
“…3I). Thus, our data consistently demonstrated that SIRT1 loss causes lysosomal de-acidification and is responsible for sEV overproduction via ATP6V1A downregulation in SEN cells, a mechanism reported for certain cancer cell types 35 .…”
Section: Sirt1 Decline Supports Deficient Lysosomal Acidification Andsupporting
confidence: 81%
“…Simultaneously, SIRT1 loss is responsible for ATP6V1A downregulation, resulting in defective lysosomal acidification and sEV overproduction by senescent cells. The data are reminiscent of a recent study which demonstrated that genetic or pharmacological inhibition of SIRT1 destabilizes the mRNA of the lysosomal V-ATPase proton pump and causes its downregulation (ATP6V1A), leading to deficient lysosomal acidification, MVB enlargement and enhanced exosomes production 35 . While our observation was mainly regarding senescent stromal cells, distinct from the discovery recently made in human breast cancer cells, a similarly occurring MVB expansion revealed by our in vitro assays suggests that senescent stromal cells somehow resemble cancer cells with regard to sEV biogenesis.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Recently, it was discovered that the NAD + ‐dependent lysine deacetylase sirtuin 1 (Sirt1) is an important regulator of exosome biogenesis in breast cancer cells. Downregulation of Sirt1 expression impaired lysosomal pH and activity, and as a consequence, resulted in more MVBs fusing with the plasma membrane and releasing exosomes, as opposed to fusing with lysosomes where their exosomal contents are degraded …”
Section: Resultsmentioning
confidence: 99%